Tidal dynamics in a changing lagoon: flooding or not flooding the marginal regions - Lopes, Carina L.
Coastal lagoons are low-lying systems under permanent changes motivated by natural and anthropogenic factors. Ria de Aveiro is such an example with its margins currently threatened by the advance of the lagoonal waters recorded during the last decades. This work aims to study the tidal modifications found between 1987 and 2012 in this lagoon, motivated by the main channels deepening which induce higher inland tidal levels. Additionally it aims to study the impact that protective walls designed to protect the margins against flooding may have in those modifications under sea level rise predictions. The hydrodynamic model ELCIRC previously calibrated for Ria de Aveiro was used and tidal asymmetry, tidal ellipses and residual currents were analyzed for different scenarios, considering the mean sea level rise predicted for 2100 and the implementation of probable flood protection walls. Results evidenced that lagoon dominance remained unchanged between 1987 and 2012, but distortion decreased/increased in the deeper/shallower channels. The same trend was found under mean sea level rise conditions. Tidal currents increased over this period inducing an amplification of the water properties exchange within the lagoon, which will be stronger under mean sea level rise conditions. The deviations between scenarios with or without flood protection walls can achieve 60% for the tidal distortion and residual currents and 20% for the tidal currents, highlighting that tidal properties are extremely sensitive to the lagoon geometry. In summary, the development of numerical modelling applications dedicated to study the influence of mean sea level rise on coastal low-lying systems subjected to human influence should include structural measures designed for flood defence in order to accurately predict changes in the local tidal properties.